ANALISIS POLA ASUH ANAK DALAM KELUARGA MILENIAL PADA MASYARAKAT MODERN - Tarisa Mustika Dewi; Meli Fauziah (Jurnal Keluarga Sehat Sejahtera, 2025)
In this practical era, it is easy for people to access the internet anywhere and anytime. This can be done by parents, especially millennials, to access information about good parenting patterns. However, if internet access is not used wisely, the opposite will happen, and bad things will easily occur in the household, both to children and parents. This study aims to examine the types of parenting styles applied by millennial parents to their children, along with the challenges faced and the perceived impact on child development. This study is a qualitative descriptive study that aims to describe the analysis of parenting styles in millennial families in modern society. The results show that millennial parents apply an authoritative parenting style that is good for children because it balances affection and discipline, but children will easily become dependent on various electronic devices such as gadgets. With the application of this authoritative approach, children will become independent, confident individuals who are able to face future challenges well. Keywords: Parenting Style, Millennial Families, Society, Modern.